DEMONSTRATIVE REFERENCE ANALYSIS IN THE JAKARTA POST HEALTH NEWS OCTOBER 2020 EDITION - Nadhilah Nur Shabrina (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Demonstrative reference is required to conduct a well-written text. Because it performs a specific function, such as referring to items in the text or signal specificity, etc., it must be clear to avoid misinterpretation of the news and make it understandable to the readers. As a result, the purpose of this qualitative study was to look into the occurrence, function, and specific pattern of demonstrative references in the Jakarta Post health news October 2020 edition. Halliday and Hasan's theory of cohesive devices was used to conduct the study. There were XXX demonstrative references found in the 10 news of health topic October 2020 edition as the object of the study. The most demonstrative reference was used by news xxx, which had 368 items, while the least was used by news xxx, which only had 2 items. The specific pattern found in the news by using the types and functions of demonstrative reference is that the news conveys cautions, preventions, suggestions, expectations, and hopes for the reader to understand the current situation conveyed by the news and build a better world after the chaos brought by the virus. Keywords: demonstrative reference, health news, The Jakarta Post